The role of bioenergy in a climate-changing world - Souza, Glaucia Mendes; Ballester, Maria Victoria R.; de Brito Cruz, Carlos Henrique; Chum, Helena; Dale, Bruce; Dale, Virginia H.; Fernandes, Erick C.M.; Foust, Tom; Karp, Angela; Lynd, Lee; Maciel Filho, Rubens; Milanez, Artur; et al. (Environmental development, 2017)
Bioenergy has been under intense scrutiny over the last ten years with significant research efforts in many countries taking place to define and measure sustainable practices. We describe here the main challenges and policy issues and provide policy recommendations for scaling up sustainable bioenergy approaches globally. The 2016 Intended Nationally Determined Contributions (INDCs defined under the UN Framework Convention on Climate Change) (UNFCCC) Conference of the Parties (COP21) will not reach global Greenhouse Gas (GHG) emission targets of 2°C. Sustainable biomass production can make a significant contribution. Substantive evidence exists that many bioenergy cropping systems can bring multiple benefits and off-set environmental problems associated with fossil fuels usage as well as intensive food production and urbanization. We provide evidence that there are many approaches to land use for bioenergy expansion that do not lead to competition for food or other needs. We should focus on how to manage these approaches on a synergistic basis and how to reduce tradeoffs at landscape scales. Priorities include successful synergies between bioenergy and food security (integrated resource management designed to improve both food security and access to bioenergy), investments in technology, rural extension, and innovations that build capacity and infrastructure, promotion of stable prices to incentivize local production and use of double cropping and flex crops (plants grown for both food and non-food markets) that provide food and energy as well as other services. The sustainable production of biomass requires appropriate policies to secure long-term support to improve crop productivity and also to ensure environmental as well as economic and social benefits of bioenergy cropping systems. Continuous support for cropping, infrastructure, agricultural management and related policies is needed to foster positive synergies between food crops and bioenergy production. In comparison to fossil fuels, biofuels have many positive environmental benefits. Potential negative effects caused by land-use change and agriculture intensification can be mitigated by agroecological zoning, best management practices, the use of eco-hydrology and biodiversity-friendly concepts at field, watershed and landscape scales. Global climate and environmental changes related to the use of fossil fuels and inequitable development make it unethical not to pursue more equitable energy development that includes bioenergy. To achieve sustainable development, competitiveness and costs of bioenergy production need to be addressed in a manner that considers not only economic gains but also development of local knowledge and social and environmental benefits. •Bioenergy can contribute to present and future societal needs in many contexts.•Existing mature technologies illustrate how sustainable bioenergy production can be expanded.•The use of integrated landscape biomass production for multiple uses including energy can decrease negative impacts.•Besides GHG reduction bioenergy brings added benefits that are not observed with other renewable energy options.